High-definition transcranial infraslow pink noise stimulation for chronic low back pain: protocol for a pilot, safety and feasibility randomised placebo-controlled trial - Ramakrishnan Mani; Dirk De Ridder; Sven Vanneste; Divya Bharatkumar Adhia; John N J Reynolds (BMJ Open)
Introduction Chronic low back pain (CLBP) is a common disabling health condition. Current treatments demonstrate modest effects, warranting newer therapies. Brain imaging demonstrates altered electrical activities in cortical areas responsible for pain modulation, emotional and sensory components of pain experience. Treatments targeting to change electrical activities of these key brain regions may produce clinical benefits. This pilot study aims to (1) evaluate feasibility, safety and acceptability of a novel neuromodulation technique, high-definition transcranial infraslow pink noise stimulation (HD-tIPNS), in people with CLBP, (2) explore the trend of effect of HD-tIPNS on pain and function, and (3) derive treatment estimates to support sample size calculation for a fully powered trial should trends of effectiveness be present.Methods and analysis A pilot, triple-blinded randomised two-arm placebo-controlled parallel trial. Participants (n=40) with CLBP will be randomised to either sham stimulation or HD-tIPNS (targeting somatosensory cortex and dorsal and pregenual anterior cingulate cortex). Primary outcomes include feasibility and safety measures, and clinical outcomes of pain (Brief Pain Inventory) and disability (Roland-Morris disability questionnaire). Secondary measures include clinical, psychological, quantitative sensory testing and electroencephalography collected at baseline, immediately postintervention, and at 1-week, 1-month and 3 months postintervention. All data will be analysed descriptively. A nested qualitative study will assess participants perceptions about acceptability of intervention and analysed thematically.Ethics and dissemination Ethical approval has been obtained from Health and Disability Ethics Committee (Ref:20/NTB/67). Findings will be reported to regulatory and funding bodies, presented at conferences, and published in a scientific journal.Trial registration number ACTRN12620000505909p.